From victims to beneficiaries: Empowerment and participation of women in the Kidunda Dam Project in Morogoro, Tanzania - Nuru , Jackson; Massoi , Lucy W.; Fundi, Saida S. (Mzumbe Unversity, 2026)
This article explores the empowerment and participation of women in developing the Kidunda Dam project in Tanzania, using the ladder of citizen participation framework to analyse their participation in decision-making, social and community engagement, and economic contributions. A qualitative research design was employed, with data collected through in depth interviews, focus group discussions (FGDs), and documentary reviews, with a thematic analysis technique to identify and analyse the key themes related to women's participation in decision-making, social and community engagement, and economic contributions. Findings reveal that women have taken on various roles, including participation in project committees and contributing to decision-making processes, promoting transparency, information sharing, and increased community engagement. Economically, women have leveraged the dam's construction to initiate business ventures, significantly contributing to the local livelihoods. This article emphasises that empowerment in mega infrastructure projects requires more than formal participation. It demands equitable engagement at every stage. In alignment with the goals of Agenda 2063, the study underscores the need for gender-sensitive infrastructure design to promote inclusive and sustainable development. Policy recommendations call for participatory practices that ensure women's contributions are recognised, valued, and integrated into development frameworks.